2012
DOI: 10.1002/oa.2230
|View full text |Cite
|
Sign up to set email alerts
|

Is Unresolved Inflammatory Angiogenesis a Mechanism for the Delayed Development of Skeletal Lesions in Syphilis?

Abstract: A recently described case of putative early tertiary syphilis in a young adult male from 6th century AngloSaxon England exhibits a distinctive endocranial pathology. A case-control study using both clinical and archaeological materials was performed to investigate a possible association of the pathology with syphilis. Scanning electron microscopy and microcomputed tomography were used to image the syphilitic case and normal cranial material. Although the pathology does seem to have an association with syphilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Infection‐associated angiogenesis has been described in a variety of pathogen infections, and this process is beneficial for pathogen survival . It is known that angiogenesis is a crucial event in the pathogenesis of syphilis . Those studies have shown that angiogenesis is one of the major pathological features of dermal lesions in primary and secondary syphilis and that it plays a role in the skeletal changes that occur in tertiary syphilis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection‐associated angiogenesis has been described in a variety of pathogen infections, and this process is beneficial for pathogen survival . It is known that angiogenesis is a crucial event in the pathogenesis of syphilis . Those studies have shown that angiogenesis is one of the major pathological features of dermal lesions in primary and secondary syphilis and that it plays a role in the skeletal changes that occur in tertiary syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…At the second stage (secondary syphilis), T. pallidum causes a plethora of clinical manifestations characterized by vascular inflammation and increased angiogenesis . In tertiary syphilis, unresolved angiogenesis is the underlying mechanism responsible for skeletal changes . Overall, angiogenesis appears to play a pivotal role in syphilis pathogenesis, as with other diseases (e.g.…”
Section: Introductionmentioning
confidence: 99%